Development of Android-Based Learning Media in Class X MA Arabic Language Subjects - Napaldi, Randika; Yusri, Meldi Ade Kurnia; Syafril, Syafril; Supendra, Dedi (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research is motivated by the minimal use of learning media to assist the learning process at MAS Muhammadiyah Lakitan due to the limited availability of learning media. Apart from that, teachers have never used Android-based learning media as support in the learning process. The aim of this research is to produce Android-based learning media that complies with development procedures and uses standard criteria of validity and practicality so that it becomes appropriate media and can assist in the learning process.The type of research used is research and development which is called Research and Development (R&D) and uses the 4-D (Four D) development model which consists of four stages, namely Define, Design (planning), Development (development) and Dissemination has been carried out in a structured and systematic manner. The validity test was carried out on 3 people, namely 2 media validators and 1 material validator. The practicality test was carried out on 20 respondents, namely class X science students at MAS Muhammadiyah Lakitan.Based on the results of the assessment by the two media validators, they obtained an average score of 4.94 which was categorized as "very valid". The results of the validation assessment from the material validator obtained an average of 4.78 which was categorized as "very valid". The results of product practicality testing by students obtained an average of 4.05 which was categorized as "practical". So based on the results of the validity and practicality assessment, it can be concluded that the media is valid and practical for use in the Arabic language learning process.